2001
DOI: 10.14411/eje.2001.048
|View full text |Cite
|
Sign up to set email alerts
|

Fitness of two phenotypes of Harmonia axyridis (Coleoptera: Coccinellidae)

Abstract: Abstract.The coccinellid H. axyridis shows considerable intraspecific variability of elytral patterns. In this paper, we suggest that a genotype that confers a specific pattern of elytra could also confer other specific autecological attributes. The aim of this paper is to compare fitness parameters of two phenotypes (aulica and nigra). Aulica is a common morph characterized by two light red areas that nearly cover the whole elytra, leaving a narrow black border, whereas nigra is completely black; the latter i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 31 publications
3
40
0
1
Order By: Relevance
“…Ongagna & Iperti (1994) state that short day conditions slow down H. axyridis development, but Table 1 in this paper indicates that at day lengths of 10.5-11.5 h larval development was faster than at day lengths of 14.5-16 h. Berkvens et al (2008) also record that the duration of pre-imaginal development of individuals of a laboratory strain of H. axyridis reared at 12L : 12D is shorter than at 16L : 8D, although larvae from a "natural" strain, cultured in laboratory for only 4 generations, in contrast, developed faster under long day conditions. Such a high intra-specific variability of various morphological and physiological parameters is often recorded for H. axyridis (Soares et al, 2001;Lombaert et al, 2008;Berkvens et al, 2008Berkvens et al, , 2010. In contrast to the duration of the larval stage, that of the pupal stage is independent of day length, which is typical of other insect species except those with a pupal diapause (Zaslavski, 1988;Saunders, 2002).…”
Section: Pre-imaginal Developmentmentioning
confidence: 91%
See 1 more Smart Citation
“…Ongagna & Iperti (1994) state that short day conditions slow down H. axyridis development, but Table 1 in this paper indicates that at day lengths of 10.5-11.5 h larval development was faster than at day lengths of 14.5-16 h. Berkvens et al (2008) also record that the duration of pre-imaginal development of individuals of a laboratory strain of H. axyridis reared at 12L : 12D is shorter than at 16L : 8D, although larvae from a "natural" strain, cultured in laboratory for only 4 generations, in contrast, developed faster under long day conditions. Such a high intra-specific variability of various morphological and physiological parameters is often recorded for H. axyridis (Soares et al, 2001;Lombaert et al, 2008;Berkvens et al, 2008Berkvens et al, , 2010. In contrast to the duration of the larval stage, that of the pupal stage is independent of day length, which is typical of other insect species except those with a pupal diapause (Zaslavski, 1988;Saunders, 2002).…”
Section: Pre-imaginal Developmentmentioning
confidence: 91%
“…However, an investigation of the total pattern of photoperiodic responses of an insect species and in particular the estimates of the threshold day lengths can be very important for predicting its phenology and potential geographic distribution, which for this coccinellid are matters of primary concern (Labrie et al, 2006;Adriaens et al, 2008;Brown et al, 2008;Koch & Galvan, 2008;Poutsma et al, 2008;Van Lenteren et al, 2008). Moreover, the recently studied populations of H. axyridis originated from Japan (Sakurai et al, 1988) and Europe (Ongagna & Iperti, 1994;Berkvens et al, 2008), and as this species is very variable (Soares et al, 2001;Lombaert et al, 2008;Berkvens et al, 2008Berkvens et al, , 2010 it would be interesting to investigate a population that originated from some other region. The Russian Far East in this context seems to be particularly interesting as it lies at the same latitude as the earlier studied SE of France (Ongagna & Iperti 1994;Iperti & Bertrand, 2001;Berkvens et al, 2008) and thus has the same dynamics of natural day length, but is characterized by colder autumns and consequently the necessity for diapause to be induced earlier (see Discussion of the data).…”
Section: Introductionmentioning
confidence: 99%
“…This species preys on more than 30 different aphid species and so was considered as a suitable candidate for efficient biological control against many pests including: aphids (see Lucas et al 2007a;Tedders and Schaefer 1994;Hodek and Honȇk 1996), Tetranychidae (Lucas et al 1997(Lucas et al , 2002, Psyllidae (Fye 1981;Michaud 2001Michaud , 2002Michaud , 2004, Coccoidea (McClure 1986), Chrysomelidae , Curculionidae (Kalaskar and Evans 2001;Stuart et al 2002) and Lepidoptera (Koch et al , 2005Musser and Shelton 2003a). Its large body size, high voracity and predation efficiency (Schanderl et al 1985;Osawa 2000;Soares et al 2001;Labrie et al 2006) as well as its good colonization efficiency (Osawa 2000; were considered good characteristics to provide successful biological control of many pests. This coccinellid seems to be an effective biological control agent; upon review of 27 studies of H. axyridis as a biocontrol agent (Lucas et al 2007a), 17 studies showed effective biological control of 16 different pest species by this coccinellid.…”
Section: Harmonia Axyridis: Where and When?mentioning
confidence: 99%
“…The ovoid shape of adults as well as bright colour may also confer a protection from predators and competitors (De Clercq et al 2003). In addition, H. axyridis is a highly polymorphic species (Soares et al 2001) and this could also help the species to be an efficient invader. Many modifications, such as elytral patterns, body shape and body size may be adaptive through imparting increased tolerance to adverse conditions (Dobzhansky 1933;Soares et al 2003a).…”
Section: Harmonia Axyridis: a Super Invader?mentioning
confidence: 99%
“…A one-229 year study involving field observations in wheat and bean crops in southern England reported an 230 absence of H. axyridis in wheat (aphid abundance was reported as low), but presence of H. axyridis 231 co-occurring with other ladybirds in bean crops (Wells 2011). Harmonia axyridis was the most 232 common aphid enemy species in bean crops and the presence of this species was correlated with 233 high aphid abundance (Wells 2011), perhaps unsurprisingly since the prey biomass required by each 234 single larva to reach the adult stage is very high (Soares et al 2001(Soares et al , 2003. 235 236 Even though H. axyridis can be considered an effective biological control agent at least from the US 237 studies, the Insurance Hypothesis predicts that control will in the long term be better achieved with 238 a diverse array of natural enemies (Loreau et al 2003).…”
mentioning
confidence: 99%